BIOTECHNOLOGY APPLICATIONS IN AGRICULTURE AND FOOD SECURITY: CURRENT TRENDS, CHALLENGES, AND FUTURE PROSPECTS - Jumayeva Yulduz Jobir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Jumayeva Yulduz Jobir qizi Abstract Global food security is facing unprecedented challenges due to rapid population growth, climate change, land degradation, and evolving pest pressures. Agricultural biotechnology offers powerful tools to address these vulnerabilities. This paper reviews the critical applications of biotechnology in modern agriculture, focusing on genetically modified (GM) crops, CRISPR/Cas9 genome editing, RNA interference (RNAi), and microbial biofertilizers. We analyze how these technologies enhance crop yields, improve nutritional profiles (biofortification), and introduce biotic and abiotic stress tolerance. Furthermore, the paper discusses the socio-economic impacts, regulatory frameworks, and public perception barriers that limit the global adoption of biotechnological innovations. Conclusively, integrating advanced biotechnology with sustainable farming practices is essential to achieving United Nations Sustainable Development Goal 2 (Zero Hunger) by 2030.